2021
DOI: 10.1002/1348-9585.12261
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fitness for work interventions for workers with low back pain: A systematic review

Abstract: Objectives Safety at work is important for workers with low back pain (LBP). This requires good job design that considers both worker capacities and work requirements, a concept called “Fitness for Work.” This systematic review aimed to evaluate the effects of fitness for work interventions on workers with LBP. Methods We searched PubMed, the Cochrane Library, and Scopus from 2000 through 2020, using relevant terms. Results We reviewed nine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Of the health conditions studied, 12 cast a wide net, seeking studies of participants with a wide range of conditions (Gensby et al, 2014 ; Hoefsmit et al, 2012 ; Lefever et al, 2018 ; NICE, 2019 ; Odeen et al, 2013 ; Schandelmaier et al, 2012 ; Tingulstad et al, 2022 ; Tompa et al, 2008 ; van Vilsteren et al, 2015 ; Venning et al, 2021 ; Vogel et al, 2017 ). Of those that were more focused, there were 11 reviews with a focus on workers with musculoskeletal conditions and/or chronic pain (Bernaers et al, 2022 ; Brewer et al, 2007 ; Carroll et al, 2010; Cochrane et al, 2017 ; Franche et al, 2005 ; Ishimaru et al, 2021 ; Neverdal, 2015 ; Oakman et al, 2016 ; Palmer et al, 2012 ; Schaafsma et al, 2013 ; van Geen et al, 2007 ), three that looked exclusively at mental health conditions (Gaillard et al, 2020 ; Mikkelsen & Rosholm, 2018 ; Nieuwenhuijsen et al, 2020 ), and one which included participants with musculoskeletal and/or mental health conditions (Cullen et al, 2018 ). There was almost no information provided about the industry or work sector in which the primary studies had been conducted, with only Brewer and colleagues mentioning some exclusions (Brewer et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the health conditions studied, 12 cast a wide net, seeking studies of participants with a wide range of conditions (Gensby et al, 2014 ; Hoefsmit et al, 2012 ; Lefever et al, 2018 ; NICE, 2019 ; Odeen et al, 2013 ; Schandelmaier et al, 2012 ; Tingulstad et al, 2022 ; Tompa et al, 2008 ; van Vilsteren et al, 2015 ; Venning et al, 2021 ; Vogel et al, 2017 ). Of those that were more focused, there were 11 reviews with a focus on workers with musculoskeletal conditions and/or chronic pain (Bernaers et al, 2022 ; Brewer et al, 2007 ; Carroll et al, 2010; Cochrane et al, 2017 ; Franche et al, 2005 ; Ishimaru et al, 2021 ; Neverdal, 2015 ; Oakman et al, 2016 ; Palmer et al, 2012 ; Schaafsma et al, 2013 ; van Geen et al, 2007 ), three that looked exclusively at mental health conditions (Gaillard et al, 2020 ; Mikkelsen & Rosholm, 2018 ; Nieuwenhuijsen et al, 2020 ), and one which included participants with musculoskeletal and/or mental health conditions (Cullen et al, 2018 ). There was almost no information provided about the industry or work sector in which the primary studies had been conducted, with only Brewer and colleagues mentioning some exclusions (Brewer et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…Scores are provided for each item on the AMSTAR‐2 checklist, alongside an overall rating. Of the 30 systematic reviews, 10 were allocated a rating of ‘High’ quality (Gaillard et al, 2020 ; Gensby et al, 2014 ; Heathcote et al, 2019 ; NICE, 2019 ; Nieuwenhuijsen et al, 2020 ; Schaafsma et al, 2013 ; Schandelmaier et al, 2012 ; van Vilsteren et al, 2015 ; Verhoef et al, 2020 ; Vogel et al, 2017 ), four of ‘Moderate’ quality (Bernaers et al, 2022 ; Cochrane et al, 2017 ; Mikkelsen & Rosholm, 2018 ; Tingulstad et al, 2022 ), four of ‘Low’ quality (Cullen et al, 2018 ; Lefever et al, 2018 ; Odeen et al, 2013 ; Tompa et al, 2008 ) and 12 of ‘Critically Low’ quality (Axén et al, 2020 ; Brewer et al, 2007 ; Carroll et al, 2010; Franche et al, 2005 ; Hoefsmit et al, 2012 ; Ishimaru et al, 2021 ; Kojimahara et al, 2020 ; Neverdal, 2015 ; Oakman et al, 2016 ; Palmer et al, 2012 ; van Geen et al, 2007 ; Venning et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most workplaces are unable to provide workers with low back pain with the full range of workplace accommodations they require. A review by Ishimaru et al 32 concluded that there were no fitness-for-work interventions with long-term positive effects for 6) 286 ( 7) Low back pain and other joint diseases 728 (11) 229 ( 9) 499 (12) Other diseases 809 ( 12) 355 ( 14) 454 (11) workers with low back pain. Third, because low back pain is susceptible to stigma, 33 if a worker with low back pain requests any additional workplace accommodations, the workplace may be less likely to provide them.…”
Section: Discussionmentioning
confidence: 99%